A comparison of intracranial volume estimation methods and their cross‐sectional and longitudinal associations with age. Issue 15 (16th June 2022) - Nerland, Stener; Stokkan, Therese S.; Jørgensen, Kjetil N.; Wortinger, Laura A.; Richard, Geneviève; Beck, Dani; van der Meer, Dennis; Westlye, Lars T.; Andreassen, Ole A.; Agartz, Ingrid; Barth, Claudia
Abstract: Intracranial volume (ICV) is frequently used in volumetric magnetic resonance imaging (MRI) studies, both as a covariate and as a variable of interest. Findings of associations between ICV and age have varied, potentially due to differences in ICV estimation methods. Here, we compared five commonly used ICV estimation methods and their associations with age. T1‐weighted cross‐sectional MRI data was included for 651 healthy individuals recruited through the NORMENT Centre (mean age = 46.1 years, range = 12.0–85.8 years) and 2410 healthy individuals recruited through the UK Biobank study (UKB, mean age = 63.2 years, range = 47.0–80.3 years), where longitudinal data was also available. ICV was estimated with FreeSurfer (eTIV and sbTIV), SPM12, CAT12, and FSL. We found overall high correlations across ICV estimation method, with the lowest observed correlations between FSL and eTIV ( r  = .87) and between FSL and CAT12 ( r  = .89). Widespread proportional bias was found, indicating that the agreement between methods varied as a function of head size. Body weight, age, sex, and mean ICV across methods explained the most variance in the differences between ICV estimation methods, indicating possible confounding for some estimation methods. We found both positive and negative cross‐sectional associations with age, depending on dataset and ICV estimation method. Longitudinal ICV reductions were found for all ICV estimation methods, with annual percentage change ranging from −0.293% to −0.416%. This convergence of longitudinal results across ICV estimation methods offers strong evidence for age‐related ICV reductions in mid‐ to late adulthood. Abstract : The choice of ICV estimation method is a possible source of bias, both in studies investigating ICV as a variable of interest and as an adjustment factor. In particular, the detection of associations with age may differ between ICV estimation methods and ICV estimates may be biased by head size, body weight, age, and sex. While cross‐sectional age associations may be partially explained by cohort differences, the convergence of longitudinal reductions for all ICV methods offers strong evidence for age‐related reductions in mid‐ to late adulthood.